Development of the Contact Lens User Experience: CLUE Scales. Issue 8 (August 2016) - Wirth, R. J.; Edwards, Michael C.; Henderson, Michael; Henderson, Terri; Olivares, Giovanna; Houts, Carrie R.
ABSTRACT: Purpose: The field of optometry has become increasingly interested in patient-reported outcomes, reflecting a common trend occurring across the spectrum of healthcare. This article reviews the development of the Contact Lens User Experience: CLUE system designed to assess patient evaluations of contact lenses. CLUE was built using modern psychometric methods such as factor analysis and item response theory. Methods: The qualitative process through which relevant domains were identified is outlined as well as the process of creating initial item banks. Psychometric analyses were conducted on the initial item banks and refinements were made to the domains and items. Following this data-driven refinement phase, a second round of data was collected to further refine the items and obtain final item response theory item parameters estimates. Results: Extensive qualitative work identified three key areas patients consider important when describing their experience with contact lenses. Based on item content and psychometric dimensionality assessments, the developing CLUE instruments were ultimately focused around four domains: comfort, vision, handling, and packaging. Item response theory parameters were estimated for the CLUE item banks (377 items), and the resulting scales were found to provide precise and reliable assignment of scores detailing users' subjective experiences with contact lenses. Conclusions: The CLUE family of instruments, as it currently exists, exhibits excellent psychometric properties. Abstract : Supplemental digital content is available in the text.